Antenna sensing of surface phonon polaritons - Neubrech, Frank; Weber, Daniel; Enders, Dominik; Nagao, Tadaaki; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
Resonant coupling between the plasmonic excitation of gold nanoantennas and phonon polaritons of a dielectric substrate−surface layer of about 3 nm thickness produces significant Fano-type signals from that layer in the infrared extinction spectrum of the fundamental antenna resonance. Compared to infrared transmittance spectra without gold antennas, the vibrational signal from the layer is about 1900 times enhanced and it is observed at surface phonon polariton frequencies of the layer, not at the transverse optical phonon frequency.
Gesehen am 10.05.2023